Trajetória do hospital dia Dr. Elger nunes: um recorte histórico da psiquiatria e saúde mental no Rio Grande do Norte - Pessoa Júnior, João Mário (2011)
In Brazil, the mental health network proposed by the Psychiatric Reform inserts the intermediate and replacement services in the pursuit of alignment or resocialization of patients with mental and behavioral disorder in the community. Was adopted, among other services, the Center for Psychosocial Care, Home Therapy, Sheltered Home, Day Hospital and psychiatric beds in general hospital. In this context, the State of Rio Grande do Norte implanted the Day Hospital Dr. Elger Nunes (HDEN) in Natal / RN in 1996, linked to State Department of Public Health. At HDEN happened a multi and interdisciplinary therapeutic work, besides being the scene of disciplinary practices, and extension projects for graduate courses in Higher Education Institutions in the city. However, with the process of decentralization of local services, the hospital was terminated by an administrative state act in 2006, leaving damage to the activities provided to users, disciplinary practices and extension activities. From this breakdown, the objective was to narrate the trajectory of HDEN through a multidisciplinary team of professionals and teachers who used it as a field of disciplinary practices. It is characterized as a documental and qualitative, backed in the technique of thematic oral history, following the phases: authorization of the interviewee, interview recording, transcription, textualization and transcreation of the material obtained. We used documents, ordinances, general reports of activities, among others, plus interviews to fifteen employees who used this service, being thirteen part of the multidisciplinary team of professionals and two graduation professors of health care area, nursing and medicine. The stories collected were organized according to the technique chosen, respecting its steps. In preparing the body subjected to ALCESTE computer program, priority was given to the vital tone for the formation of categories and classes elected by the program, structured in three thematic areas. In the first axis, called Trajectory of HDEN, were recalled the beginning of its activities, the steps of that time, their activities, and its actors - users, families, professionals, and teaching practices. The second axis has dealt with the process of extinction of HDEN, rescuing the feelings of employees, the main reasons given at the time and immediate postextinction scenario. And the third axis revealed in an articulated form the situation of mental health in Natal / RN, listing to the challenges and prospects for the psychosocial care, starting from the trajectory of HDEN with emphasis on activities. Moreover, the trajectory of HDEN provides recognition of the historical basis outlined in the constitution of the network of substitute services present in the current scenario of psychosocial care in the city of Natal and in RN.